2021
DOI: 10.1088/1742-6596/1767/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Detection with Local Binary Pattern and CNN Classifier

Abstract: The present work proposes two novel approaches namely One Dimensional adaptive average Local Binary Pattern (1-D AaLBP) and One-Dimensional adaptive difference Local Binary Pattern (1-D AdLBP) for feature extraction from EEG signals and Convolutional Neural Network (CNN) for classification of EEG signals. Both the proposed feature extraction methods are computationally easy to implement. In the first step the histograms are formed from the extracted patterns, after that feature vectors of the histogram are giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…/ The author(s) of this article declare that the materials and methods used in this study do not require ethical committee permission and/or legal-special permission. EEG nöronlar tarafından üretilen beynin elektriksel aktivesinin ayrıntılarını içeren bir sinyaldir [11]. Bu sinyaller zaman serisi verileridir ve zaman alanından öznitelikler çıkarılarak EEG modeli analiz edilir [12].…”
Section: Etik Standartların Beyanı (Declaration Of Ethical Standards)unclassified
“…/ The author(s) of this article declare that the materials and methods used in this study do not require ethical committee permission and/or legal-special permission. EEG nöronlar tarafından üretilen beynin elektriksel aktivesinin ayrıntılarını içeren bir sinyaldir [11]. Bu sinyaller zaman serisi verileridir ve zaman alanından öznitelikler çıkarılarak EEG modeli analiz edilir [12].…”
Section: Etik Standartların Beyanı (Declaration Of Ethical Standards)unclassified
“…The proposed model outperformed other methods with a sensitivity of 96.84% and an absolute specificity of 99.66% on the CHB-MIT dataset. In this work [28], the author presented two innovative strategies for extracting features from EEG data and classifying them using Convolutional Neural Networks (CNNs). The results of the studies showed that the suggested technique outperforms the others in terms of sensitivity, specificity, classification accuracy, and runtime.…”
Section: Literature Surveymentioning
confidence: 99%
“…A CNN is a type of feed-forward neural network that shows robust performances in many image classification and pattern recognition tasks [43,44]. The main distinction between a CNN and a normal neural network is that a CNN benefits from the properties of the local connective, shared weights, hierarchical features, and pooling [45].…”
Section: Convolutional Neural Networkmentioning
confidence: 99%